BEAUTY CONCEPT REPRESENTED IN WARDAH “FEEL THE BEAUTY” VIDEO ADVERTISEMENT : SEMIOTICS APPROACH - Salindeho, Stefany Ellen; Fadilah, Eka; Kurniawan, Yulius (Seminar Nasional Ilmu Terapan, 2023)
This study is focused to analyze the advertisement for a beauty product called Wardah. The objectives of the study are to find out the signs that contained in Wardah’s “Feel the Beauty” campaign advertisement. To analyze the signs, the researcher uses the theory of semiotics from Charles Sanders Peirce. This theory is used because it helps to explain three types of sign content in the advertisement, which is icon, index, and symbol. This study uses descriptive qualitative approach. The result of this study shows that the writer find out, from one advertisement that analysis, the writer finds out the three types of signs, such as icons, index and, symbols, the number of icons that has been found out in the advertisement is 6 (six) data, which all referring to the introduction of Wardah products that claimed can help enhance the confidence of women who use the product. The number of indexes in the advertisement is 4 (four) data, which all data referring to the confident beauty that can improve by using the Wardah product, the number of symbols in the advertisement is 5 (five) data.